The perceptions of policymakers on earthquake mitigation: A qualitative study in an Iranian context. Issue 3 (28th February 2020) - Heidari, Samaneh; Vatankhah, Soudabeh; Tourani, Sogand; Heidari, Mohammad
Abstract : Purpose: The purpose of this study identified the priorities, challenges and different aspects of the mitigation phase according to policymakers for planning and better management of reducing risk within the cultural, religious, social and political conditions of Iran. Design/methodology/approach: In the present qualitative study, 19 policymakers in different levels of the disaster management organizations were selected based on purposive sampling. Semi-structured and face-to-face interviews were used to identify the participants' views. The findings were analyzed using thematic analysis. Findings: The present situation and the challenges of the mitigation phase were the main themes in this study. Risk perception, training and media were the sub-themes. Political, legal, social and cultural challenges of the mitigation phase were also sub-themes. Originality/value: The findings of this study indicated that different aspects should be considered to minimize the risk of earthquake. In addition, all kinds of media, including visual, written, audio, instrumental, group and multimedia, should be used for enhancing public awareness so that readiness for earthquakes can be considered as a permanent mission of the citizens, who are always concerned about earthquakes.